World watch Geography skills book 2 grade 7 - Moorcroft, Christine (Karachi : Oxford university press, 2023)
The World Watch Geography Grade 7 Skills Book is a companion resource designed to help students develop and strengthen their geographical skills through practical exercises and activities. It focuses on enhancing the application of the concepts learned in the main geography textbook by providing hands-on learning experiences.
Keywords: Geography : Skills book; Oxford : Grade 7